(untitled) (CIPEEX, 2022)
THE PRESENT WORK SEEKS TO ANALYZE THE MAIN EFFECTS OF INAPPROPRIATE AND ILLEGAL USE OF PRESERVATION AREAS, THE MAIN OBJECTIVE IS TO DEMONSTRATE THE SHORT AND LONG TERM EFFECTS AND THE ROLE OF THE STATE IN FACING THESE PROBLEMS. THE DISORDERED GROWTH OF CITIES WITHOUT ADEQUATE CITY PLANNING, THE COMPRESSION AND MIGRATION OF THE POPULATION FROM RURAL AREAS TO URBAN AREAS, HAS CAUSED THE ACCELERATED GROWTH OF CITIES TO SUCCUMB TO INFRASTRUCTURE OR BASIC SANITATION. BRAZIL IS A COUNTRY RICH IN POPULATION DIVERSITY, FAUNA AND FLORA AS WELL AS IN ITS TERRITORIAL EXPANSION, HOWEVER THE COUNTRY’S GRANDEUR ALSO BRINGS WITH IT SOCIAL INEQUALITIES, WHICH RESULTS IN PERMANENT PRESERVATION INVASIONS. IN VIEW OF ARTICLE 225 CAPUT OF THE FEDERAL CONSTITUTION OF 1988, THE DISORDERLY GROWTH OF CITIES WAS CREATED THE MASTER PLAN WITH THE PURPOSE OF MAKING AN ADEQUATE PLANNING OF CITIES WITH A POPULATION FROM 20 THOUSAND INHABITANTS, BECAUSE THE EFFECTS ON APPS WILL FROM MILD TO ALMOST IRREVERSIBLE EFFECTS ON THE ENVIRONMENT, AMONG OTHERS. THE PRESENT WORK EVALUATES THE STUDY OF SCIENTIFIC ARTICLES, BIBLIOGRAPHIC JOURNALS, MAMMOGRAMS AND BOOKS AS THE MAIN EFFECTS OF IRREGULAR CONSTRUCTIONS IN PERMANENT PRESERVATION AREAS, HIGHLIGHTING MAINLY THE SOCIAL AND ENVIRONMENTAL EFFECTS AND ANALYZING THE MAIN MEASURES ADOPTED BY THE GOVERNMENT IN ORDER TO PRESERVE AREAS OF PERMANENT PRESERVATION AS WELL AS SOCIAL PROGRAMS IN ORDER TO PRESERVE SOCIAL AND ENVIRONMENTAL RIGHTS.